The Effectiveness Of Early Mobilization On Intestinal Peristalsis In Post-Caesarean Section Patients Undergoing Spinal Anesthesia At Cilacap Regional Hospital - Dhea Yulianita Dhea Yulianita; Endiyono Endiyono (International Journal of Health Engineering and Technology, 2026)
Caesarean section (CS) with spinal anesthesia often causes paralytic ileus due to intestinal peristalsis inhibition, which slows patient recovery. This study aims to examine the effectiveness of early mobilization on intestinal peristalsis frequency in post-CS patients at Cilacap Regional General Hospital. Using a quasi-experimental pretest-posttest design with a control group, the population was post-CS patients with spinal anesthesia in the Mawar Room (December 2025), a sample of 44 respondents via purposive sampling (Slovin formula, e=5%). Instruments included observation sheets, stethoscopes, and informed consent; data analysis used Shapiro-Wilk, Wilcoxon Signed Rank, and Mann-Whitney. The results showed a significant increase: 4 hours post-CS from 3.66 to 4.59 times/minute (p<0.001, Z=-4.667); 6 hours from 7.09 to 8.48 times/minute (p<0.001, Z=-5.756), with superiority at 6 hours (p=0.000). It was concluded that early mobilization was effective in accelerating the recovery of intestinal peristalsis, especially at 6 hours post-operatively.